Polymerase chain reaction-Based clonality analysis of cutaneous B-cell lymphoproliferative processes (Clinics, 2010)
INTRODUCTION: The differential diagnosis of B-cell lymphoproliferative processes remains a challenge for pathologists, dermatologists and oncologists, despite advances in histology, immunohistochemistry and molecular biology. OBJECTIVE: Evaluate aid and limitations of clonality analysis in the diagnosis of primary cutaneous B-cell lymphomas and B-cell pseudolymphomas. METHODS: This study included 29 cases of B-cell lymphoproliferative processes classified as primary cutaneous B-cell lymphomas (13), B-cell pseudolymphomas (6) and inconclusive cases (10) using histology and immunohistochemistry. The clonality analysis was performed by polymerase chain reaction analysis of immunoglobulin light chain and heavy chain rearrangements. RESULTS: DNA quality was shown to be generally poor; eight samples were inadequate for polymerase chain reaction analysis. The results showed monoclonality in eight of the primary cutaneous B-cell lymphomas and polyclonality in four of the B-cell pseudolymphomas. In addition, monoclonality was shown in two of the inconclusive cases by histology and immunohistochemistry, demonstrating the utility of polymerase chain reaction as an ancillary diagnostic tool for primary cutaneous B-cell lymphomas. DISCUSSION: The low quality DNA extracted from these cases demanded the use of an IgH protocol that yielded small fragments and IgK. Both methods used together improved detection. CONCLUSION: Use of the two protocols, immunoglobulin heavy chain FR3-trad and immunoglobulin light chain-Kappa Biomed protocols for clonality analysis improved diagnostic accuracy.